Revision of Janeirona Distant, 1911 (Hemiptera: Pentatomidae: Ochlerini) with the description of four new species from Brazil - Sampaio, Vinícius Gomes; Oliveira, Giulia Valadão De; Campos, Luiz Alexandre (Zootaxa, 2024)
Janeirona Distant, 1911 is a Neotropical pentatomid genus restricted to South America that was recently transferred from Pentatominae to Ochlerini (Discocephalinae). Janeirona was described for one species, and during the 20th century other five species were allocated in the genus. In this study we redescribe Janeirona and its known species, and propose two new synonyms: Serdia stali Kormilev, 1956 as junior synonym of Janeirona insignis Distant, 1911, and Janeirona asaroana Brailovsky, 1988 as junior synonym of Janeirona costalimai (Pirán, 1962). We describe four new species: Janeirona aurea Sampaio & Campos sp. nov., Janeirona flavipes Sampaio & Campos sp. nov., Janeirona roellae Sampaio & Campos sp. nov., and Janeirona stenosa Sampaio & Campos sp. nov.. An identification key to the species and distribution maps are given.